Presentations of Routine Dental Interventions in Children over a Six-Year Period - Samia Aboujaoude; Balsam El Noueiri (The Scientific World Journal)
Aim. To evaluate over a six-year period, the prevalence of the dental procedures in primary and mixed dentitions, in males and females. Materials and Methods. A retrospective descriptive study on dental treatments in primary and mixed dentitions was conducted in the Department of Pediatric Dentistry at the Faculty of Dental Medicine, Lebanese University, from 2015 to 2020. The total number of children was 1291. Data were classified and reviewed according to the dentition type, gender, and type of dental treatment. Results. The number of children decreased from 741 for the period 2015–2017 to 550 during the period 2018–2020 (279 males and 271 females). No significant association was found between the admission periods and the genders. A significant relationship was found between the number of treatments performed in both genders and the dentition types (p value = 0,015). Males were slightly more likely than females to present for the treatment in mixed dentition (54.58% versus 45.2%, respectively). Results portrayed a significant relationship between surgical treatment and gender (p value = 0.049). However, no significant relationship between gender and other treatment types was noted. The comparison between the 2 time frames and the types of treatments showed a significant association in composite fillings (p value = 0.043), extractions (p value < 0.0001), sealants (p value = 0.039), preventive resin restoration (p=0.011), pulp therapies (p value < 0.0001), pediatric crowns (p value < 0.0001), and surgical interventions (p value = 0.013). A nonsignificant relationship was recorded for the appliances and composite crowns (p value = 0.45 and 0.14, respectively). Conclusion. The present study points out the implications of the COVID-19 outbreak and Lebanon’s economic collapse on children’s dental status, with the number of children receiving dental care dropping remarkably. A decrease in all types of dental procedures was noted in mixed dentition, whereas an increase in dental treatments related to aggravated carious lesions was reported in primary dentition. More medical and financial aids are required to encourage and support parents’ attitude towards children dental care during unprecedented crises.